Experimental Study of Gas Microbubbles on Oil‐Infused Wrinkled Surfaces - Leo James; Christopher Vega‐Sánchez; Priya Mehta; Xuehua Zhang; Chiara Neto (Advanced Materials Interfaces)
Abstract Lubricant‐infused surfaces (LIS) have been shown to reduce hydrodynamic drag to a greater extent than theoretically expected, making them attractive candidates for microfluidic applications. The presence of nano‐ and micro‐bubbles has been found to explain this property, but this observation is not widely acknowledged. This work investigated how the volume and distribution of lubricant in wrinkled Teflon LIS affects bubble durability. The lubricant is depleted from LIS by repeated immersion through an air–water interface, as well as by shearing, gravity drainage and spreading. The bubbles are imaged using confocal fluorescence microscopy at different levels of infused lubricant. The lubricant encasing the bubbles on LIS prevented bubbles from shrinking over several hours, compared to uninfused superhydrophobic Teflon wrinkles, in which bubbles more rapidly shrunk in height, typically within 30 min. The size of bubbles is independent of lubricant volume, likely due to lubricant redistribution underwater. These findings point toward the possibility of a short‐term stabilization of bubbles on structured surfaces for drag reduction applications through the use of lubricant.